1999
DOI: 10.1001/jama.281.7.650
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Hypertrophic Cardiomyopathy in a Regional United States Cohort

Abstract: In a regionally selected patient population most closely resembling the true disease state, HCM did not significantly increase the risk of premature death or adversely affect overall life expectancy. Prevailing misconceptions of HCM as a generally unfavorable condition may largely be related to the skewed patient referral patterns characteristic of tertiary care centers. Hypertrophic cardiomyopathy is nevertheless a highly complex disease capable of serious clinical consequences and premature death in some pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
308
11
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 472 publications
(339 citation statements)
references
References 30 publications
12
308
11
8
Order By: Relevance
“…The survival rates in these 2 studies are much better than previously reported in children with HCM (3% to 8%) thought to be idiopathic. 22,23,25 Our experience parallels that in adults, in which the annual incidence of sudden death in HCM patients referred to tertiary care centers was reported to be 3% to 5%, but subsequent population studies in adults indicated a much lower annual mortality of 0.1% to 1%, [27][28][29][30][31] with asymptomatic adults at even lower risk. 32 Referral bias appears largely responsible for these differences.…”
Section: Outcome In Ihcmsupporting
confidence: 63%
“…The survival rates in these 2 studies are much better than previously reported in children with HCM (3% to 8%) thought to be idiopathic. 22,23,25 Our experience parallels that in adults, in which the annual incidence of sudden death in HCM patients referred to tertiary care centers was reported to be 3% to 5%, but subsequent population studies in adults indicated a much lower annual mortality of 0.1% to 1%, [27][28][29][30][31] with asymptomatic adults at even lower risk. 32 Referral bias appears largely responsible for these differences.…”
Section: Outcome In Ihcmsupporting
confidence: 63%
“…[1][2][3][4][5][6][7]19,21,22 The importance of septal thickness as a predictor of SCD remains contentious. Spirito et al 5 reported no incidence of SCD in 400 patients with septal thickness Ļ½15 mm compared with a 2% annual risk in patients with a septal thickness Ļ¾30 mm.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In the adult population with HCM, specific risk factors for SCD include younger age at diagnosis, family history of HCM, massive left ventricular (LV) hypertrophy, prior ventricular tachycardia (VT) or cardiac arrest, and underlying mutations within specific genes. 4 -6 Children with HCM are a unique population compared with adults, and it is important to independently determine prognostic risk factors for adverse clinical outcomes in this group, such as death, arrhythmia, cardiac symptoms, and decreased exercise capacity.…”
mentioning
confidence: 99%
“…Without other predictors of outcome, except for an outflow gradient no less than 30 mmHg, 23,24 we began treatment with ablocker, although some HCM centers favor verapamil or class Ia antiarrhythmic agents. 25 This case needs close observation because transition to the dilated phase has been reported in a patient with HCM with midventricular obstruction.…”
Section: Discussionmentioning
confidence: 99%